Infestation Levels Of Tropical Bed Bug (Cimex Hemipterus F.) (Hemiptera: Cimicidae) In Peninsular Malaysia And Their Resistance To Conventional Insecticides And Entomopathogenic Fungi - Zahran, Zulaikha (2016)
Nowadays majority of pest control industries are having difficulties in battling bed bugs, specifically in workers’ dormitories and residential houses. Long-term treatment of many insecticides classes including chemical or non-chemical active ingredients are necessary at least three to four times for complete eradication. Here, a research is conducted to survey bed bug infestations across Peninsular Malaysia by collecting samples from residential houses, dormitories, hotels and motels and flats and apartments. The survey was carried out in 11 states; Pulau Pinang, Perlis, Perak, Kedah, Terengganu, Kelantan, Pahang, Selangor, Negeri Sembilan, Melaka, Johor and federal territory of Kuala Lumpur. Active bed bugs infestation was detected in 38 sites from the overall 181 surveyed sites.